Representasi Nilai Budaya Tari Klasik Jayengrana Kasumedangan Sebagai Atraksi Wisata Budaya - Ratu Nurul Fahmi Aulia; Irena Novarlia; Rifqi Asy’ari (Academy of Education Journal, 2026)
Jayengrana dance is a form of classical dance that represents the rich local cultural values of the Sundanese people, especially in the Sumedang region. In the midst of modernization and globalization, traditional dance faces challenges in the preservation and regeneration of art actors, so efforts are needed to strengthen the role of traditional arts in the context of culture and tourism. This study aims to examine the existence of the Jayengrana Dance as a local cultural heritage and analyze its potential as a cultural tourism attraction that has educational value. The research uses a descriptive qualitative approach with ethnographic methods. Data was collected through field observations of the rehearsal and performance process, in-depth interviews with the performers, and documentation of dance activities. Data analysis was carried out by categorizing findings based on cultural values, social functions, and the role of dance in the development of cultural tourism. The results of the study show that the Jayengrana Dance not only functions as a medium of artistic expression, but also as a means of transferring moral, historical, and cultural values to the younger generation. In addition, this dance has significant potential to be developed as a cultural tourism attraction that is able to attract the interest of the public and tourists. Continued support from governments, cultural institutions, and the tourism sector is needed through the promotion, training, and integration of traditional dance in formal tourism and education packages.